2005
DOI: 10.3149/jms.1401.47
|View full text |Cite
|
Sign up to set email alerts
|

Western Heterosexual Masculinity, Anxiety, and Web Porn

Abstract: This article is an examination of nine pornographic Web sites. Web porn is important because the Internet increases men's access to pornography. The pornography presented on these Web sites is first examined in terms of the way that it manifests important continuities with pornography delivered in other ways. Central to these continuities is the way that pornography manifests the anxiety that is here taken to be fundamental to the acquisition of Western heterosexual masculinity or male identity. An important d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 22 publications
2
30
0
2
Order By: Relevance
“…Some anecdotal evidence demonstrated that men (and to a smaller degree women) may be drawn to pornography when lonely and sexually frustrated (as reported in Marriott, 2003) but it was also proposed that pornography may be a harmless pleasure and healthy way of realizing sexual fantasy that could bring some couples closer together (Featherstone, 2005). Cook (2006) stated that, in pornography, person-to-person communication could be simulated, which could be desirable to some and troublesome to others. Indeed, pornography has been blamed for its destructive effects on intimacy (e.g., Bergner & Bridges, 2002), specifically for those couples who already have problems concerning trust and sex (Featherstone, 2005).…”
Section: Research and Theories On A Specific Link Between Closeness Amentioning
confidence: 95%
See 3 more Smart Citations
“…Some anecdotal evidence demonstrated that men (and to a smaller degree women) may be drawn to pornography when lonely and sexually frustrated (as reported in Marriott, 2003) but it was also proposed that pornography may be a harmless pleasure and healthy way of realizing sexual fantasy that could bring some couples closer together (Featherstone, 2005). Cook (2006) stated that, in pornography, person-to-person communication could be simulated, which could be desirable to some and troublesome to others. Indeed, pornography has been blamed for its destructive effects on intimacy (e.g., Bergner & Bridges, 2002), specifically for those couples who already have problems concerning trust and sex (Featherstone, 2005).…”
Section: Research and Theories On A Specific Link Between Closeness Amentioning
confidence: 95%
“…It has been claimed that intimacy could be risky to men because the boundaries of the masculine self were fragile (Cook, 2006) and that pornography could provide a place in which men found their authority unchallenged and got even for lost dreams (Marriott, 2003), but such assertions tended to generalize. Investigating adolescents' sexual disclosure on the Internet, Chiou (2006) established that, unlike in real life, their online sexual self-disclosure depended on the level of anonymity and de-individuation and, also, that male participants were more likely to engage in sexual self-disclosure.…”
Section: Research and Theories On A Specific Link Between Closeness Amentioning
confidence: 97%
See 2 more Smart Citations
“…Such endurance represents control over nature—both in the form of women's bodies and of nature within—and stages this battle for control in terms of a competitive contest among men. Indeed, Ian Cook (2006) points out that because Internet porn presents its viewers with a world in which there are an endless number of women who are available for sex, the effect is “… to demand that men conquer increasing numbers of women to demonstrate their manliness”; moreover, the repeated display of well‐endowed male bodies “… reinforces the idea that women can only be satisfied by men with large penises who can maintain erections for indefinite periods” (p. 56). Under the rule of the performance principle, the male body is turned into a competitive instrument of alienated labor.…”
Section: Masculinity Phantasy and The Bodymentioning
confidence: 99%